RELIGIOSITY, RELIGIOUS COPING, AND MENTAL HEALTH OF GENERATION Z STUDENTS FROM THE PERSPECTIVE OF THE PSYCHOLOGY OF RELIGIOUS DEVELOPMENT - Nabila Dewi Yulianti; Siti Norhidayah; Annisa Annisa; Siti Milawati; Surawan Surawan (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2026)
Students’ mental health is a crucial aspect of education as it affects their ability to regulate emotions, adapt, and cope with academic demands. Generation Z faces various challenges, including academic pressure, changing social interactions, and exposure to digital environments. From the perspective of the psychology of religious development, religiosity and religious coping are viewed as psychological resources in dealing with stress. This study aims to analyze the relationship between religiosity, religious coping, and the mental health of Generation Z students. The study employed a quantitative approach with a correlational design. The sample consisted of 36 students selected using a saturated sampling technique. Data were collected through Likert-scale questionnaires and analyzed using descriptive statistics and multiple linear regression with SPSS. The results show that religiosity and religious coping simultaneously have a significant relationship with mental health. However, partially, both variables do not show a significant effect. These findings indicate that spiritual aspects contribute to mental health but are also influenced by other psychosocial factors. Therefore, the integration of religious values in educational settings is important to support students’ mental health.